Littérature de jeunesse et maîtrise de la langue - Christiane Connan-Pintado (Strenae)
The field of publication of children's book offers many playful fictions about the language and some of them have taken their place on the lists of literature published by the Ministry of National Education for primary schools, from kindergarten. As these works play with words, reading them can help to build and consolidate different language skills. While these stories are distinguished by their emphasis on language, they are nonetheless fictional, inviting the reader to follow the adventures of characters and, therefore, are part of the literary field by their encyclopaedic, ideological and/or aesthetic scope. However, although these books offer the teacher the opportunity to combine the objectives of literary reading with those of language mastery, it must be said that the balance between these two valences is hardly respected and that fiction is most often used as a tool for building linguistic skills. This is the question that we ask, based on basis of two bodies of research: on the one hand, the editorial field for young people of works based on the fictionalisation of the language; on the other hand, the educational use of a few works. The question is how to make the most of the playful and cultivated resources of a production for young people which aims to introduce young readers to literature while at the same time allowing them to experience the richness of their language.